Correlation between disease severity and respiratory variables in patients with liver cirrhosis and ascites (Brazilian Journal of Health Research, 2020)
Introduction: Liver cirrhosis is a chronic disease that triggers several complications. Among the complications, we highlight the accumulation of extravascular fluids and ascites, which causes increased intra-abdominal pressure and impairs respiratory mechanics. Objective: Investigating the impact of cirrhosis in association with ascites on respiratory variables, signs and symptoms. Methods: 14 cirrhotic patients with ascites were evaluated. The following evaluations were carried out after clinical data collection: vital signs measurement, respiratory pattern evaluation, thoracic and abdominal cirtometry measurements, as well as pulmonary function (based on a ventilometer), dyspnea degree (numerical scale) and fatigue level evaluations (visual analog scale). Data were analyzed through statistical Student’s t-test, whereas Pearson’s correlation test was used for correlation analysis between variables. Significance was established at p value
Keywords: Liver cirrhosis; Ascites; Respiratory system